Correlation Between Breast Density Classification with Sugar Levels for Iraqi Women - Nouri, Areej; Al-Kaisy, Aedah Z. (Journal of Neonatal Surgery, 2025)
Breast density, a critical parameter in mammographic imaging, refers to the proportion of fibroglandular tissue to fatty tissue within the breast. It is a significant factor in breast cancer risk assessment, as higher breast density is associated with an increased risk of breast cancer and can obscure lesions on mammograms, complicating early detection. The American College of Radiology classifies breast density into four categories: A (almost entirely fatty), B (scattered areas of fibroglandular density), C (heterogeneously dense), and D (extremely dense).This study aims to investigate the relationship between breast density classification and blood sugar levels among Iraqi women. The methods 100 women in this study. Mammography was utilized to determine the breast density. The results statistically significant between breast density classification , age and suger levels tests while not significant with body mass index for both breast. conclusion: our results indicate that the Iraqi women with breast density classification showed a decrease in age (for both breasts).other results breast density an increase with increase of suger levels of patients